Genetic Influence of PTPN22 R620W Polymorphism in Tuberculosis (2005)
The PTPN22 gene codes for an intracellular lymphoid-specific phosphatase (Lyp) that has a negative regulatory effect on T-cell activation. Because Lyp is an important molecule involved in the inflammatory response, and its levels are increased in cells that participate in the immune response against Mycobacterium tuberculosis, we hypothesized that the functional PTPN22 C1858T polymorphism could be a genetic factor predisposing to the development of tuberculosis (TB). Accordingly, we undertook an association study in which 113 patients with pulmonary TB and 161 matched healthy controls stratified by the tuberculin skin test (TST) were examined. Significant skewing was observed when T allele frequencies of patients with TB and all controls were compared (P = 0.04, odds ratio = 0.3; 95% confidence interval = 0.08-1.04) and frequencies of patients with TB and TST+ healthy controls were compared (P = 0.01, odds ratio = 0.2; 95% confidence interval = 0.05-0.79). No stratification was detected between patients and control samples. These results suggest that the T allele may be a factor protecting against development of TB once the immune system recognizes M. tuberculosis (i.e., TST+ individuals), whereas the C allele may be a risk factor for development of overt TB. The results also indicate that an association opposite that between the PTPN22 polymorphism and TB exists between TB and autoimmunity. © 2006 American Society for Histocompatibility and Immunogenetics.